PERANAN ORANGTUA SEBAGAI WALI, PEMBIMBING, DAN PENDIDIK PADA PERKEMBANGAN ANAK DALAM PERSPEKTIF PENDIDIKAN AGAMA ISLAM - Moh Rifai (Premiere Educandum : Jurnal Pendidikan Dasar dan Pembelajaran, 2011)
Family, parents, wives, children, are an entity of a small social unit of mankind. Family is an inherent and natural social body which willingly or reluctantly will occur among moslem families. Parents’ roles as the educator, guide of the children and family in order that they grow up to become ultimate moslems in the sense of insan kamil.